2018
DOI: 10.1002/jlb.4ab0417-152rrr
|View full text |Cite
|
Sign up to set email alerts
|

CD64 on monocytes and granulocytes in severe acute bronchiolitis: Pilot study on its usefulness as a bacterial infection biomarker

Abstract: The CD64 receptor has been described as a biomarker of bacterial infection. We speculated that CD64 surface expression on monocytes and granulocytes of children with severe acute bronchiolitis (SAB) could be altered in cases of probable bacterial infection (PBI) determined using classical biomarkers (procalcitonin and C-reactive protein, leukocyte count, and radiographic findings). A prospective observational pilot study was conducted from October 2015 to February 2016 in children admitted for pediatric critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…2 d). CD64 is an FCγ receptor of immunoglobulin G and increases surface expression on monocytes and granulocytes in conditions of infection and systemic inflammation [17] . In cirrhosis, both CD169 + and CD169 − monocytes had increased surface expression of CD64 in comparison with healthy controls, while CD169 + monocytes had higher expression than CD169 − monocytes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 d). CD64 is an FCγ receptor of immunoglobulin G and increases surface expression on monocytes and granulocytes in conditions of infection and systemic inflammation [17] . In cirrhosis, both CD169 + and CD169 − monocytes had increased surface expression of CD64 in comparison with healthy controls, while CD169 + monocytes had higher expression than CD169 − monocytes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Más recientemente se han venido estudiando nuevos biomarcadores para diferenciar infecciones virales y bacterianas (2) (23) (24) (25) (26) (27), pero muchas instituciones, al igual que la nuestra, carecen de los recursos para realizarlos. Otras técnicas de aislamiento microbiológico e imágenes como la fibrobroncoscopia, el lavado bronquioalveolar, el cepillado bronquial, la tomografía de tórax y la resonancia magnética del tórax solo están indicadas en circunstancias especiales (11).…”
Section: Introductionunclassified
“…However, in bacteria-infected individuals, the expression of CD64 on neutrophils can be markedly elevated (> 10-fold) within a few hours, which allows differentiation between resting and activated neutrophils [ 11 ]. Many studies have demonstrated that the expression of CD64 on neutrophils measured as an index had higher sensitivity and specificity for infection: The neutrophil CD64 (nCD64) index significantly increases in bacteria-infected diseases, such as sepsis, systemic infection, bronchitis, and bacterial peritonitis [ 6 , 12 ].…”
Section: Introductionmentioning
confidence: 99%